Peripheral ossifying fibroma in the maxillary arch - V A Trasad; G M Devarsa; V V Subba Reddy; N D Shashikiran (Wolters Kluwer Medknow Publications, 2011)
Many types of localized reactive lesions may occur on the gingiva, including focal fibrous hyperplasia, pyogenic granuloma, peripheral giant cell granuloma and peripheral ossifying fibroma. Peripheral ossifying fibroma is a gingival growth, usually arising from interdental papilla and represents up to 2% of all lesions that are biopsied. Other terms used to describe this lesion include peripheral cementifying fibroma, peripheral fibroma with cementogenesis, peripheral fibroma with osteogenesis, peripheral fibroma with calcification, calcified or ossified fibrous epulis and calcified fibroblastic granuloma. This article reports a case of a 10 year old male child with an unusually large peripheral ossifying fibroma in the left maxillary alveolar ridge which showed recurrence after the surgical treatment.